Mechanosensitivity may be enhanced in skeletal muscles of spinal cord–injured versus able‐bodied men. Issue 4 (30th August 2014) - Yarar‐Fisher, Ceren; Bickel, C. Scott; Kelly, Neil A.; Windham, Samuel T.; Mclain, Amie B.; Bamman, Marcas M.
ABSTRACT We investigated the effects of an acute bout of neuromuscular electrical stimulation–induced resistance exercise (NMES‐RE) on intracellular signaling pathways involved in translation initiation and mechanical loading–induced muscle hypertrophy in spinal cord–injured (SCI) versus able‐bodied (AB) individuals. AB and SCI individuals completed 90 isometric knee extension contractions at 30% of maximum voluntary or evoked contraction, respectively. Muscle biopsies were collected before, and 10 and 60 min after NMES‐RE. Protein levels of α7‐ and β1‐integrin, phosphorylated and total GSK‐3α/β, S6K1, RPS6, 4EBP1, and FAK were assessed by immunoblotting. SCI muscle appears to be highly sensitive to muscle contraction even several years after the injury, and in fact it may be more sensitive to mechanical stress than AB muscle. Heightened signaling associated with muscle mechanosensitivity and translation initiation in SCI muscle may be an attempted compensatory response to offset elevated protein degradation in atrophied SCI muscle. Muscle Nerve 50: 599–601, 2014